Sejarah Penempatan dan Perubahan Sosial Muslim Hui di Xi'an, China: History of Hui Muslim Settlement and Social Change in Xi'an, China - Long, Ahmad Sunawari; Mat Zain, Farid (Journal of Al-Tamaddun, 2025)
This article explores the historical development and social transformation of the Hui Muslim community in Xi’an, China, one of the earliest and most significant Muslim settlements along Silk Road, China. Drawing upon historical sources, field research, and recent academic studies, the paper highlights the arrival of Islam through diplomatic and military missions from the 7th century onward, particularly through the efforts of Sa’d ibn Abi Waqqas and later Islamic troops aiding Chinese dynasties. It examines the evolution of the Hui identity, emphasizing their integration with Han Chinese culture while maintaining Islamic faith and practices. The research traces key phases: the foundation of the Muslim Quarter (Huimin Jie), the development of religious schools and sects (e.g., Gedimu, Yihewani, and Salafi), and the impact of critical events like the Dungan Rebellion. Xi’an emerges as both a strategic and symbolic center for Islam in China, featuring architectural, linguistic, and cultural syncretism. The article concludes that despite historical marginalization and socio-political upheavals, the Hui of Xi’an have sustained their religious identity and communal resilience, contributing richly to Chinese Islamic heritage.